Peptide platform for 3D-printed Ti implants with synergistic antibacterial and osteogenic functions to enhance osseointegration - Chenying Cui; Yifan Zhao; Jingyu Yan; Ziyang Bai; Guning Wang; Yingyu Liu; Yurong Xu; Lihong Zhou; Kaifang Zhang; Yanling Mi; Binbin Zhang; Xiuping Wu; et al. (Materials Today Bio)
Bone defects caused by trauma, infection, or tumors present a major clinical challenge. Titanium (Ti) implants are widely used due to their excellent mechanical properties and biocompatibility; however, their high elastic modulus, low surface bioactivity, and susceptibility to infection hinder osseointegration and increase failure rates. There is an increasing demand for implants that can resist bacterial infection while promoting osseointegration. In this study, we developed a peptide platform to engineer a multifunctional 3D-printed Ti implant (3DTi) modified with a fusion peptide composed of minTBP-1 (targeting peptide), KR-12 (antibacterial peptide), and GFOGER (adhesion peptide), termed 3DTi-NFP. This design enables specific targeting, localized delivery, prevention of peptide release into circulation, and functional integrity through linker retention. In both in vitro and in vivo infected bone defect models, 3DTi-NFP implants demonstrated excellent biocompatibility and achieved over 90 % bactericidal efficiency against S. aureus and E. coli. The implants reduced bacterial colonization while enhancing adhesion, proliferation, and differentiation of bone marrow mesenchymal stem cells (BMSCs), significantly upregulating osteogenic genes and protein expression. Transcriptome sequencing further explored the molecular mechanisms underlying the synergistic effects of 3DTi-NFP, revealing activation of the focal adhesion and PI3K-Akt signaling pathways-key contributors to cell adhesion, matrix formation, and new bone formation. Overall, this study provides a promising strategy to improve the long-term success of Ti-based implants, with significant potential for tissue regeneration and clinical applications.